مقاصد الشريعة في المعاملات المالية ودورها في تحقيق العدالة الاقتصادية: Maqashid Syariah in Financial Transactions and Its Role in Achieving Economic Justice - Zifamina, M. Zainul Haq Fiddin; Alam, Azhar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The purpose of this research is to study the role of sharia maqashid in regulating financial transactions and achieving economic justice, through an analysis of the basics of maqashid that are the foundation of the Islamic financial system, as well as explaining their impact on the protection of rights, achieving a balance between individual interests and public interests, and reducing the practice of injustice and economic exploitation. This study uses an analytical descriptive method, with the application of an inductive approach to trace sharia texts and the opinions of scholars, as well as a comparative approach to highlight the differences between maqashid's view of Islamic economics and some conventional economic views. This study concludes that sharia maqashid, especially in safeguarding wealth, realizing justice, and eliminating difficulties, is a comprehensive ethical and legislative framework that contributes to the development of a fair and sustainable financial system, as well as being able to face contemporary economic challenges. The authenticity of this research lies in the relationship between maqashid theory and the practical application of modern financial transactions, which strengthen economic justice and inclusive development.